2020
DOI: 10.1021/acsenergylett.0c02140
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the New Role of an Ethylene Carbonate Solvation Shell in Rechargeable Metal Ion Batteries

Abstract: Electrolytes play a critical role in controlling metalion battery performance. However, the molecular behavior of electrolyte components and their effects on electrodes are not fully understood. Herein, we present a new insight on the role of the most commonly used ethylene carbonate (EC) cosolvent both with the bulk and at the electrolyte-electrode interface. We have discovered a new phenomenon that contributes to stabilizing the electrolyte, besides the well-known roles of dissociating metal salt and forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 64 publications
4
120
0
Order By: Relevance
“…This process is detrimental because lithium can react with the EMC solvent due to less reduction stability of the Li + -EMC pair. [42] Our finding not only interprets the observed lithium on the graphite anode in Figure 4a but also explains the root cause of the reduced cycling stability of the battery in the EMC electrolyte (Figure S3b). Note that some side-reaction products can be observed in the MA electrolyte resulting in the less formation of lithium dendrite, which is attributed to a low Li + de-solvation energy (Figure 6b) and the byeffect of the polarization is less than that in the EMC electrolyte (weaker interaction between Li + and MA solvent or anion in Figure 5g, j).…”
Section: Interfacial Modelsupporting
confidence: 72%
“…This process is detrimental because lithium can react with the EMC solvent due to less reduction stability of the Li + -EMC pair. [42] Our finding not only interprets the observed lithium on the graphite anode in Figure 4a but also explains the root cause of the reduced cycling stability of the battery in the EMC electrolyte (Figure S3b). Note that some side-reaction products can be observed in the MA electrolyte resulting in the less formation of lithium dendrite, which is attributed to a low Li + de-solvation energy (Figure 6b) and the byeffect of the polarization is less than that in the EMC electrolyte (weaker interaction between Li + and MA solvent or anion in Figure 5g, j).…”
Section: Interfacial Modelsupporting
confidence: 72%
“…As the polymer chain is made up of repeating units derived from the BA monomers, we use BA molecular as the repeating unit structure in the polymer and further simulate the coordination environment of Na + in the GPE. It has been reported that EC molecule could competitively coordinate with alkali metal ion and dominate the coordinative situation in the first solvation shell, [ 34 ] so the EC molecular was used to simulate Na + solvation structure in LE and GPE. As shown in Figure 4d, Na · OC has lower binding energy than the other two possible coordination configurations in LE, and a similar result is also exhibited when EC molecule was replaced by BA (Figure 4e), which means that Na · OC is the main coordination structure, and it is consistent with the Raman results.…”
Section: Resultsmentioning
confidence: 99%
“…[ 32 ] Thus, the solvation structure plays an important role in determining the reduction stability of solvents in electrolytes. [ 33–37 ] According to the theory of frontier molecular orbital, in the ISC structure solvent molecules will draw electrons from the anions to increase the lowest unoccupied molecular orbital (LUMO) energy level, making it harder for solvent molecules to get electrons and to be reduced. The ISC structure also promotes the generation of anion‐derived SEI, which can effectively prevent the decomposition of solvents.…”
Section: Introductionmentioning
confidence: 99%